Structural Equation Modeling Partial Least Square (SEM-PLS) Untuk Membandingkan Kondisi Public Speaking Anxiety Mahasiswa Soshum dan Saintek - Sabina Chairun Najwa; Natasya Dwi Ovalingga; Hanifah Nazhiroh; Rizki Akbar; Fadhilah Fitri (UNP Journal of Statistics and Data Science, 2023)
Public speaking is a communication skill to deliver opinion or massage to the audience. Public speaking anxiety, caused by various factors. Social and science students have differences in culture and learning systems. Therefore, students in both educational clusters have their own ways of overcoming communication barriers. This study aimed to identify factors that influence public speaking anxiety in social and science students at Padang State University. The method used is the Structural Equation Model Partial Least Square (SEM-PLS) to understand the influential factors in more detail and minimize analysis errors caused by missing values and multicollinearity due to diverse samples. The results of the analysis are path diagrams for structural models and outer loading tables. If the < value is 0.7, then recalculation is carried out so that a new model is formed. The feasibility of the social science family model was obtained 35% and the scientific science family was 36.5%. The effect of latent or exogenous variables in this study is weak. Social students have higher levels of speech anxiety than science students. This is influenced by humiliation, unfamiliar role, and negative result factors. In science students, the influencing factors are humiliation, preparation, and unfamiliar Role.